Factors affecting target INR levels in homebound and ambulatory patients who use warfarin - Ozge Tuncer; Ayca Asma Sakalli; Mustafa Ozan Gursoy (Journal of the Pakistan Medical Association)
Objective: To investigate the rates of reaching target international normalised ratio levels and the factors affecting these rates in patients undergoing warfarin therapy.